Disparity in the access to kidney transplantation for sensitized patients in the state of Sao Paulo-Brazil - Perosa, Marcelo; Ferreira, Gustavo F.; Modelli, Luis G. [UNESP]; Medeiros, Marizete P.; Neto, Soraia R.; Moreira, Frederico; Zampieri, Fernando G.; de Marco, Renato; Bortoluzzo, Adriana B.; Venezuela, Maria K. (Elsevier, 2021)
Highly sensitized (HS) patients accumulate on deceased donor kidney transplantation (DDKT) waitlists worldwide due to matching difficulty and inequity of allocation policies. Current situation of HS patients on KT waitlist in Brazil has not been published. All patients enrolled on the KT waitlist of the State of São Paulo from 2002 to 2017 were retrospectively assessed. Patients were divided into eight groups according to their degree of sensitization, PRA of 0%, >0–40%, >40–80%, >80–85%, >85–90%, >90–95%, >95–98% and > 98%. Cumulative incidence curves for transplantation or mortality/removal from waitlist were estimated by competing risk. Among 50,249 waitlisted candidates, 1247 prioritized, 2467 with age < 18 or > 75 years and 4152 submitted to living-donor KT were excluded from the analysis, remaining 42,383 patients. There were 29,664(70%) PRA 0%, 5611(13.2%) PRA > 0–40%, 3442(8.2%) PRA > 40–80%, 507(1.2%) PRA > 80–85%, 564(1.3%) PRA > 85–90%, 825(1.9%) PRA >90–95%, 859(2%) PRA > 95–98% and 911(2.2%) PRA > 98%. There was a progressive increase in the need of prioritization, waiting time for KT or on waitlist and time on dialysis as PRA increased (p < 0.001). Probability of DDKT clearly increased as PRA decreased so that PRA 0% candidates were much more likely to be transplanted compared to PRA > 98% patients(HR:13.02, p < 0.001). Waiting list mortality/removal was higher among PRA > 0–40%(HR1.05,p = 0.03), PRA > 90–95%(HR:1.10,p = 0.05), PRA > 95–98%(HR:1.26,p < 0.001) and PRA > 98%(HR:1.09,p = 0.05) patients compared to PRA zero candidates. HS patients in Sao Paulo-Brazil required greater prioritization due to lack of venous access, longer dialysis and waitlist times, lower probability of DDKT and higher rates of waitlist mortality/removal. We confirmed the disparity of access to KT among HS patients in Sao Paulo-Brazil, indicating the need of new strategies that optimize transplantation for this subcategory of patients.
Keywords: Highly sensitized; Kidney transplantation; Sensitization; Transplantation; Waiting list